Problematika Pendidikan Dalam Wacana Eksistensialisme Martin Heidegger - Anwar Ma’rufi; Khoirun Nisa; Mohamad Madum (Departement of Mathematics Education, 2023)
Pragmatic modern society has a tendency to reduce humans to machines that have no will. Existentialism seeks to place humans according to their nature rather than relying on the role of machines, so Heidegger's thought is present which completely diverts metaphysical and epistemological questions to ontological questions. Heidegger did not specifically review educational concepts. However, because his thoughts pertain to the fundamental of issues, namely being/being, he can permeate a wide variety of fields of study, including those relating to discussions of educational problems. So, in this study the aim is to discuss and present Heidegger's ideas that intersect with educational concepts. The research method used is the method of library research (library research). This type of research relates to books, documents, journals and various other important references related to the title that I have analyzed to draw relevant conclusions according to the point of view. The conclusion of this research is humans are unique from one another depending on how they are able to have space and time authentically. The positive side of Heidegger's thought is that education in Heidegger's existentialism discourse must be able to find the authenticity of each student by changing the direction and goals of education, teacher concepts, student concepts, curriculum, and learning materials.